Observation of nanoscale magnetic fields using twisted electron beams - Vincenzo Grillo (Nature Portfolio, 2017)
Beyond high resolving power, electron microscopy can be used to study both the electronic and magnetic properties of a sample. Here, Grillo et al. combine electron vortex beams with holographic detection to measure out-of-plane nanoscale magnetic fields.